Analisis literatur tentang faktor penyebab dan dampak stres akademik pada mahasiswa - Anggraini, Annisa Rani (Maliki Interdisciplinary Journal, 2025)
College students often experience stress. There are many factors that cause stress faced by college students, one of which is the academic load that is considered heavy. The purpose of this study is to find out what are the factors that cause and the impact of stress experienced by college students. In this study, Literature Review (LR) was used to review previous research studies. Through a search using google scholar, 37 research articles and journals were found. Of the 37 studies, 13 research journals were relevant and in accordance with the criteria. From 13 journals, it was found that there are several factors that cause academic stress in college students. Stress also has an impact on college students’ physical, behavioral, emotional, and cognitive conditions. In addition, another impact of stress makes college students experience academic procrastination by delaying their work and experiencing cyberloafing, namely by accessing the internet outside of lecture topics. One of the coping stress carried out is using a smartphone to open social media and games to relieve fatigue so that individuals who experience stress have the potential to experience addiction.